Laser interferometric characterization of a vibrating speaker system - Freschi, A. A.; Caetano, N. R.; Santarine, G. A.; Hessel, R. (Amer Assoc Physics Teachers Amer Inst Physics, 2003)
An experiment that combines opto-mechanical and electrical measurements for the characterization of a loudspeaker is presented. We describe a very simple laser vibrometer for evaluating the amplitude of the vibration (displacement) of the speaker cone. The setup is essentially a Michelson-type interferometer operated by an inexpensive semiconductor laser (diode laser). It is shown that the simultaneous measurements of three amplitudes (displacement, electrical current, and applied voltage), as functions of the frequency of vibration, allow us to characterize the speaker system. The experiment is easy to perform, and it demonstrates several useful concepts of optics, mechanics, and electricity, allowing, students to gain an intuitive physical insight into the relations between mathematical models and, an actual speaker system. (C) 2003 American Association of Physics Teachers.